Progress towards achieving the 17 sustainable development goals: the role of governance, democracy and well-being - Marjorie Morales-Casetti; Marco Bustos-Gutiérrez; Ángela Araya-Muñoz; Vicente Zúñiga-Valdebenito (Discover Sustainability)
Abstract The literature identifies governance, democracy, and well-being as non-economic factors favorable to achieving the 2030 Agenda. However, little has been explored about the relationship between these factors on the 17 SDGs and the axes of the Agenda: People, Planet, Prosperity, Peace, and Partnership. The study seeks to contribute along this line, identifying the factors related to governance, democracy, and well-being that influence the achievement of the 17 SDGs. Using statistical models, we estimate the influence of five independent variables: government effectiveness, the status of democracy, personal autonomy and individual rights, welfare regime, and subjective well-being on achieving each of the 17 SDGs. The findings, which highlight the crucial role of the welfare regime and subjective well-being, particularly in the objectives of the Person, Planet, and Peace axes, provide a significant advancement in our understanding of sustainable development and practical insights for policymakers and practitioners. The welfare regime is positive and significant in ten of the fourteen analyzed models, while subjective well-being is significant in six. Contrary to expectations, government effectiveness is only positive in some SDGs and adversely affects the Planet axis, highlighting the need to integrate sustainability criteria into public policies. For its part, democracy negatively affects several SDGs, possibly due to factors such as political instability and electoral cycles. The article's findings provide critical insight into how governance, democracy, and well-being can facilitate or, in some cases, hinder sustainable development, guiding the development of more balanced and sustainable policies in the future.